(untitled) (Journal of the College of Education for Women, 2019)
The Rwandan author of comfort chests and verse pleasure of the most important historians of the Seljuks in the sixth century AH / twelfth century and belongs to the mostly ethnic scientists family has won favor with the Sultans of the Seljuks until he became the most famous Markhém is his main source of research sources with respect to the political and social history the Seljuks and the relationship of the Seljuk sultans of the Abbasid caliphs in Baghdad.The book included the history of the Seljuks from the time of statehood in the fifth century AH / atheist century AD until the death of the Sultan Tgrl bin Arslan year 590 AH / 1193 AD and then shed Akhawarzmeyen, and touched the author at the end of the book in separate chapters to some of the social, cultural and technical issues.Characterize the book and smooth easy manner adopted the historical narrative of events differed from the writings of historians Arab Muslims in not mentioning the sources, has hired the author style literary often formed the stories and parables, governance and hair, a big part of the size of the book as well as an exaggeration author in praise of the Seljuks.